PENGARUH PROMOSI PENJUALAN PAKAIAN WANITA ALMIRA SHOP DI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN FOLLOWERS - Anggraini, Dameria; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
One of the advances in mobile phone technology is smart phone and iOS which is a smart phone operation system. It is used to support the means of communication where one of the facilities is instagram. The instagram is used to do trading some products (online shop). This study aimed to find out the sales promotion effect of Almira women clothing shop on instagram toward followers purchasing decision. In S-O-R theory, material object was human whose components’ souls are: attitudes, opinions, behaviors, cognition, affection, and konasi. According to this theory, organism results a particular behavior in certain stimulation condition. The effect appeared is a specific reaction toward specific stimulation. So, one can expect and predict compatibility between message and communicant reaction.This study used qualitative research whichdescribed and explained a problem with generalized result. The research method was survey method which used questionnaire as the data collection technique. The population of this study was the followers of Almira Shop Pekanbaru instagram which has 7883 followers on its account. The researchersetthe samples of this study were the Instagram account of Almira Shop followers who ever made purchasing. Using the slovin formula, there were 80 people of the followers qualified as the sample. In this study, Double linier regression with SPSS 16.00 program was used to analyze the data.Based on the result, it was obtained that the probability value(p value) of sales promotion variabel (0.001) <α =0.1. It means that women clothing sales promotion of Almira Shop on Instagram influenced the purchasing decisions of the folowers. The influence contribution ofwomen's clothing sales promotion of AlmiraShop in Instagram toward folowers purchasing decisions was 13.4%. Based on the result, the value of 13.4 was extended from 0.00 to 0.199 which was at the extremely weak category.In short, the influence of women clothing sales promotion of Almira shop on instagram toward the followers’ purchasing decision was weak. It was because the lack of trust between Almira shop and its followers and lack of sales promotion; such as contest, money-returned offer and discount in order to stimulate the followers to keep making purchasing.Keyword: Sales Promotion, Buying Decision, Instagram and Onlineshop